Diagnosis, management, and follow-up of extensive dermoid cyst of the submental region - Débora Menezes Regis; John Lennon Silva Cunha; Celeste Sánchez-Romero; Maria Alice Carvalho da Cruz Ramos; Ricardo Luiz Cavalcanti de Albuquerque-Júnior; Bruno Torres Bezerra (University of São Paulo, 2019)
Dermoid cyst (DC) is a cystic lesion of developmental origin and uncertain etiology that rarely affects the floor of the mouth. We report a case of a large lesion found in the submental and submandibular region in a 25-year-old male patient. Computed tomography revealed extensive hypodense lesion in the submental and submandibular space without peripheral enhancement. The microscopical analysis showed a cystic cavity lined by orthokeratinized stratified squamous epithelium. The cystic capsule was composed of dense fibrous connective tissue containing cutaneous attachments, such as sebaceous and sweat glands. The diagnosis of DC was made. The differential diagnosis of expansive sublingual lesions can be clinically challenging due to the similarity with several lesions frequently observed in this region. Herein, we describe a case of extensive DC arising in the floor of the mouth, presenting clinical, imaging, and microscopical features.